The Role of Principals in Enhancing Teacher Well-being in Schools in Rural Communities - Kwatubana, Siphokazi (Journal of Contemporary Issues in Education, 2024)
This study sought to understand the factors that teachers and school management team members perceived as having the potential to boost teacher well-being in rural schools and the role the principal plays in promoting teacher well-being. A stratified sample of school managers and teachers from a rural high school in the Mopani district of the Limpopo province participated. A total of fourteen semi-structured individual interviews were conducted with seven teachers, yielding four enablers to teacher well-being and three roles which principals could play to support teacher well-being. The findings revealed that strong principal-teacher relationships, disengaging from work to socialize, adaptability, and a green school physical environment promote teacher well-being. The role of the principal in supporting teacher well-being is multi-faceted, encompassing the creation of a positive school culture and traditions, developing and maintaining a conducive green school environment, and promoting teacher adaptability.